A case report of a cochlear implant infection – A reason to explant the device?. (2nd September 2016) - Skrivan, Jiri; Drevinek, Pavel
Abstract : Clinical presentation : Case history of a paediatric patient with a cochlear implant and a surgical site infection that developed as a result of acute otitis media is presented. Intervention : After conservative management including wound debridement it was decided to explant a functioning device. Objective and importance : In a number of cases, it is necessary to remove the infected albeit functioning device, especially in the event of formation of the biofilm has occurred. It is necessary to review and evaluate the methods with which these major complications are routinely managed with the aim to increase the survival ratio for the implanted device.